Determinants of Corporate Trade Credit: An Empirical Study on Korean Firms - Kim, Woo Sung (International Journal of Economics and Financial Issues, 2016)
This study is designed to determine the motives for trade credit in Korean firms. Based on data collected from 14,660 firm-year observations running from 1992 to 2011 on the Korean Stock Exchange, this paper finds strong evidence on determinants of trade credit based on financial characteristics. The principal result is that older firms with larger size, lower growth, and higher profits tend to extend accounts receivable. This evidence, while consistent with the access to financing and price discrimination hypothesis, is difficult to reconcile with the growth hypothesis. Second, this paper provides evidence that firms with larger size and greater leverage, as well as young firms, appear to use accounts payable. This finding, while consistent with the financial constraint hypothesis, is difficult to harmonize with the financing and growth hypothesis. The paper contributes to the argument about trade credit motives. It may help managers in making financial policy concerning improving firm value in the Korean market. Keywords: trade credit, accounts receivable, accounts payable JEL classification: M41